Diversity Analysis of Catechol 2, 3-dioxygenase in POPs Metabolizing Bacteria using In-silico Approach - Fatima Muccee (Current Trends in OMICS, 2023)
The persistent nature of persistent organic pollutants (POPs), lipophilicity, and volatility has resulted in their high concentration, not only in environmental resources but also in living organisms. Their complete removal is possible only by mineralization using enzyme-based strategies. Catechol 2, 3-dioxygenase is reportedly involved in the degradation of a wide variety of POPs. This study was designed to determine the diversity of this enzyme among highly efficient bioremediating bacteria. Seven bacteria belonging to genera acinetobacter, pseudomonas, burkholderia, stutzerimonas, and paraburkholderia were targeted. Sequences of the enzyme were retrieved from Uniprot database and analyzed via ProtParam, CELLU, and SOPMA tools and AlphaFold database. The enzyme was found to be cytoplasmic. The physicochemical properties of the enzyme were recorded as pI 4.75 – 5.50, aliphatic index (73.41 – 88.55), instability index (24.98 – 43.37), and GRAVY (-0.209 – 0.511). The secondary structure attributes were recorded to be α-helix (30.13 – 37.30), extended strand (18.27 – 21.54), β-turn (5.14 – 6.95), and random coil (38.33 – 42.95). All the proteins showed complex folding except in Pseudomonas sp strain EST1001. These properties may be exploited during the selection, purification, manipulation, and cloning of the enzyme for efficient bioremediation.